Homem macho machucado : a relação entre o sofrimento de homens e os padrões da masculinidade hegemônica na perspectiva da gestalt-terapia - Bianca Pessoa Costa (2022)
The present study has as objective to understand the relation between the ideals of masculinity hegemony and the psychological distress of the men in the light of Gestalt-Therapy. It was used a descriptive methodology to achieve the study results corresponding to the objectives and, as for the means, the methodological tool seek was the bibliographic search with a non systematized data collection. It was possible to understand how the concept of the masculinity hegemony is built on the individual’s life according to the relation with the context which is insert in. The existence of a plurality in the expressions of masculinity also stood out in this study, which refutes the ideia that it has a right way of being a man. Furthermore, it was concluded that the suffering was proved to exist to the men that corresponds to the standards of masculinity and also to the ones that contradict it. It must be observed the need of further studies that come up with awareness observations about being a man, in a way that the rapprochement of the individuals with their authenticities can be facilitated.